Effect of Stratification on Seed Germination and Early Seedling Growth of Some Wild Almond (Prunus scoparia Spach.) Genotypes from Kuzestan (Iran) - N. Fathi; M. Heidari; K. Behnam Far (علوم و فناوری بذر ایران, 2017)
At present experiment, the effects of moist stratification duration (at 7+1 oC) on seed germination and early seedling growth of three genotype of wild almond (Prunus scoparia) from Khuzestan province (southwest of Iran) were investigated. The seeds of P. scoparia were selected from wild almond trees in Masjed Sloeyman, Izeh and Dezful regions. After tip pinching, seeds of each genotype were stratified for 0, 15, 30 and 45 days. Results of germination test showed that stratification for 45 days increased seed germination percentage, seed germination rate and early seedling growth of all three genotype. The highest germination percentage were 68, 69 and 71 for Masjed Sloeyman, Izeh and Dezful, respectively. Seedling growth indices of each genotype (vigor index, root and shoot length and seedling dry weight) were increased after stratification for 30 to 45 days and also differences among responses of genotypes were statistically significant. The lowest germination vigor (0 and 43.75, respectively) were observed in seeds of Masjed Sloeyman and Dezful without stratification after 15 days stratification and for seeds of Masjed Sloeyman (84.5) after 30 days. Overall, results indicated that the stratification for 45 days after removal of seed coat and origin of seed significantly affect the germination and early seedling growth of P. scoparia genotypes form Khuzestan.